Development of Practical Guidebooks for Physics Education Students at Cenderawasih University - Wilda Wijayani Pamangin; Bonefasius Yanwar Boy; Silvia Anggri Wijaya; Widyaskara Mangando (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
This study aims to (1) examine the validity characteristics of the developed practical guidebook; (2) analyze the responses of practitioners regarding the developed practical guidebook. The laboratory manual to be developed is significantly innovative in that it combines inclusive and flexible instructional design with active and contextual learning approaches. The manual also includes pedagogical aspects to help students not only understand physics but also internalize how to teach science effectively in the future. This research is a type of research and development (R&D) aimed at developing a manual. According to Thiagrajan, development research is based on the 4-D model, namely Define, Design, Development, Disseminate, or the 4-P model, which consists of the definition stage, the design stage, the development stage, and the dissemination stage, which in this study is limited to the development stage only. The results of the study show that the developed practicum guidebook has met the validity standards for testing with an internal consistency coefficient of 0.97. In addition, based on the results of the student response analysis, it is known that the developed practicum guidebook is in the very practical category with a practicality percentage of 88%. This score shows that the developed practical guidebook is considered practical by students for use in practical activities.